La prescripción en el procedimiento especial de ejecución coactiva en la corporación nacional de telecomunicaciones CNT E.P. en el Ecuador - Espinosa Solano, Gabriela Lisset (2025)
The research examines the validity of registering indigenous justice resolutions in the Property Registry of Cayambe, Ecuador, between 2017 and 2023. Using a mixed-methods approach, the study evaluates 40 registered resolutions to determine their compliance with jurisdictional competence, due process, and property norms. Interviews with registry officials further reveal the criteria and challenges associated with these registrations. The findings highlight a significant gap between the constitutional recognition of indigenous jurisdiction (Article 171) and the absence of a specific regulatory framework within the registry system. This misalignment leads to tensions, inconsistent practices, and challenges such as insufficient due process verification and decisions exceeding indigenous jurisdiction. While the Cayambe Registry addressed this issue by creating a specialized registry book, ambiguities in Constitutional Court rulings continue to limit property decisions to community lands, weakening collective land protections. The study concludes that a harmonized framework is essential to uphold indigenous autonomy, ensure legal security, and integrate these resolutions into the registry system. Recommendations include establishing clear guidelines for indigenous resolution registrations, training registrars on intercultural principles, and fostering dialogue between jurisdictions to strengthen legal pluralism in Ecuador.